Electric Fields Induced by Transcutaneous and Intracranial Current Injections in the Rat Brain - Asan, Ahmet S. (Conf Proc IEEE Eng Med Biol Soc, 2018)
As a non-invasive brain stimulation technique, transcranial electrical stimulation (TES) and specifically the transcranial direct current stimulation (tDCS) has gained popularity in recent years for treatment of a wide variety of cognitive and neurological disorders. Recent studies have shown that TES can alter the motor cortex excitability. Animal studies to demonstrate the underlying mechanisms of TES are clearly lacking in literature. Clinical studies have agreed on the critical role of the current intensity and the montage of the electrodes for the treatment to be effective. In this study, we used a rat model for in vivo investigation of the vertical electrical (E) Held distribution due to electrodes placed over the skin and through a craniotomy hole. A mono-phasic current pulse was used as a substitute for DC currents by taking advantage of primarily resistive properties of the brain tissue at low frequencies. The electrical potentials induced by the current pulses were recorded with penetrations at Omm, 2mm, and 4mm away from the stimulation electrode. The results showed that the E-field was maximum immediately under the anodic electrode and decreased both in the vertical and horizontal directions rapidly by distance. The magnitude of the electric field varied from tens of mV/mm to a fraction of mV/mm by distance for a 100 μA stimulus amplitude. The results also show that the E-field amplitudes and distribution strongly depend on whether the stimulus electrode is placed over the skin or into a craniotomy hole.